2016
DOI: 10.1021/acs.jpclett.6b00947
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Two Triplet-Pair Intermediates in Singlet Exciton Fission

Abstract: Singlet fission is an excitation multiplication process in molecular systems that can circumvent energy losses and significantly boost solar cell efficiencies; however, the nature of a critical intermediate that enables singlet fission and details of its evolution into multiple product excitations remain obscure. We resolve the initial sequence of events comprising the fission of a singlet exciton in solids of pentacene derivatives using femtosecond transient absorption spectroscopy. We propose a three-step mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

29
345
1
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 216 publications
(381 citation statements)
references
References 41 publications
29
345
1
6
Order By: Relevance
“…If the rate at which the two triplets within 1 (T 1 T 1 ) diffuse apart in the material is faster than singlet-quintet spin-mixing, a process that usually takes place in nanoseconds, then the direct formation of (T 1 +T 1 ) from 1 (T 1 T 1 ) may occur. However, if the triplet excitons separate on a timescale comparable to spin-mixing, the exponential decrease in J SQ as the distance between the two spin-correlated triplet states increases will result in singlet-quintet mixing4041. In contrast, if two pentacenes are covalently linked, J SQ is controlled by the electronic structure of the linkage between them.…”
Section: Discussionmentioning
confidence: 99%
“…If the rate at which the two triplets within 1 (T 1 T 1 ) diffuse apart in the material is faster than singlet-quintet spin-mixing, a process that usually takes place in nanoseconds, then the direct formation of (T 1 +T 1 ) from 1 (T 1 T 1 ) may occur. However, if the triplet excitons separate on a timescale comparable to spin-mixing, the exponential decrease in J SQ as the distance between the two spin-correlated triplet states increases will result in singlet-quintet mixing4041. In contrast, if two pentacenes are covalently linked, J SQ is controlled by the electronic structure of the linkage between them.…”
Section: Discussionmentioning
confidence: 99%
“…Current investigations into the intermediates in singlet fission, e.g. bound triplet pair excimers 99 or strongly interacting triplet pairs, 136 etc., enabled by various monomer or dimer configurations 97,[137][138][139][140][141][142] will shed light on the dielectric environment needed to stabilize triplet excitons. Such interdisciplinary approaches will reveal the fundamental structure-property relationships affecting triplet diffusion in thin films, and ultimately enable the engineering of optoelectronic devices making use of multi-excitonic processes.…”
Section: Discussionmentioning
confidence: 99%
“…The most widely used technique to probe singlet fission has been transient absorption (TA) spectroscopy, but most studies to date have only identified spectral features assigned to S 1 and T 1 states, and there has been little explanation as to why these TA peaks nearly always overlap ( 12 16 , 35 , 36 ). Exceptions to this prevalent practice can be found in the recent work of Sanders et al ( 11 ) who found, in pentacene dimers, an excited-state absorption (ESA) peak at ~690 nm whose magnitude is strongly correlated with the strength of intertriplet electronic coupling and in the work of Pensack et al ( 37 ) who observed near-infrared (IR) (1200 to 1400 nm) ESA in pentacene aggregates assigned to 1 (TT) but not to the triplet pair labeled 1 (T…T), which has lost electronic coherence but retained spin coherence. These two examples reveal the presence of spectroscopic signatures for the 1 (TT) state in TA, but the origins of these transitions and their relationships to the energetics of the 1 (TT) state remain unknown.…”
Section: Introductionmentioning
confidence: 99%